Risk of failure in existing RC balcony and strength verification under degradation phenomena. (January 2020) - Campione, G.; Cannella, F.
Highlights: Safety conditions of reinforced concrete (RC) balconies. Degradation phenomena caused by carbonation, chlorides attack or water infiltration. Typical damages of balconies with detachments of plaster and bricks expulsion. Analytical expressions to predict flexural and shear strength of balconies. Abstract: In the present paper, the safety conditions of reinforced concrete (RC) balconies subject to degradation phenomena caused by carbonation, presence of chlorides or water infiltration were examined. After a brief review of the typical damages of balconies occurring with detachments of plaster and bricks expulsion, some cases of collapses of balconies recently occurred were presented. Therefore, a calculation model was proposed for a hand verification of the flexural and shear strength of existing corroded T beams cast in place of lightened RC orthotropic slabs forming the balcony and for the calculus of deflection including slippage of steel bars. Diffused and pitting corrosion on steel bars, compressive concrete strength degradation, and concrete bond strength degradation are included in the model. This approach is simple and can be applied based on the experimental information available (carbonation test, chloride content, measurement of the pitting in the bar, a gravimetric method for general corrosion) or by utilizing analytical expressions calibrated on knowledge of the corrosion current intensity determined by linear polarization resistance measurement (LPR).